Study of Daucuscarota ssp. Sativus and Butea monospermato analyse their Applicability in Pharmaceutical Industry as Antimicrobial Agents - Nikhil Bhalla; Vijay Kumar; Susmita Shukla (International Journal of Phytomedicine, 2018)
Human Beings have been using plant products to heal the Wounds and Diseases from the inception of humankind. Even when it was not known that microorganisms exist, People have been using antimicrobial agents prepared from plants. These antimicrobial products were prepared by extracting the plant in a suitable solvent. Antimicrobial property is conferred to plants by the presence of various phytochemicals which are the products of several Secondary metabolic pathways. The aim of this project was to decipher the potential use of Daucus carota ssp. Sativus and Butea monosperma in the pharmaceutical industry. In this research, Qualitative phytochemical screening and antimicrobial potential of Black carrot and Kamarkas has been studied. Black carrot showed good antimicrobial activity against A. brasiliensis, E. coli and S. enterica, arranged in descending order of the Slope obtained in each antimicrobial assay. Phytochemical screening showed the presence of Flavonoids, Soluble Phenolic Compounds, Naphthoquinone and traces of Saponins and Alkaloids. The Kamarkas showed antimicrobial activity against S. aureus and to some extent against A. brasiliensis. Phytochemical analysis of Kamarkas showed positive for all phytochemicals.